Hubungan antara Tingkat Stres dengan Tingkat Keparahan Akne Vulgaris pada Siswa Kelas XII SMA Negeri 5 Denpasar: English - Gede Nengah Osa Jayadiningrat; Luh Gede Pradnyawati; Made Sudarjana (Aesculapius Medical Journal, 2023)
Acne vulgaris is defined as an inflammation of the pilosebaceous follicles that generally occurs in adolescents and young adults. Stress is one of the causes that is multifactorial. Stress can increase androgen hormones as well as increased sebum production and also stimulates keratinocytes. Increased production of high sebum accompanied by an increase in keratinocytes can lead to the appearance of acne vulgaris. This study was aimed at determining the relationship between stress levels and the severity of acne vulgaris of SMA Negeri 5 Denpasar students. This study used a quantitative analysis method design with a cross sectional approach. Purposive sampling technique was used to select research subjects and 212 twelfth grade students of SMA Negeri 5 Denpasar were selected as the sample. Data was collected using the DASS-21 questionnaire and physical examination of the facial area. It was analysed using technique of univariate and bivariate analysis using the Spearman correlation test. Univariate results showed that the majority of students were female (65.1%), 18-year-old (53.5%), with mild stress level (63.2%), and having mild acne (81.6%). The results of the bivariate analysis showed that there was a relationship between stress levels and the severity of acne vulgaris of the twelfth grade students of SMA Negeri 5 Denpasar (p = 0.001) with a strong correlation level and a positive direction (r = 0.571). Therefore, it can be concluded that there is a relationship between stress levels and the severity of acne vulgaris of twelfth grade students of SMA Negeri 5 Denpasar.